“There’s some colonial in my postcolonial”: Community Development Workers’ Perspectives on Faith-based Service Learning in a Guatemalan Context (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
Faith-based relief and development organization Mennonite Central Committee (MCC) has been involved in the country of Guatemala since 1976 when they responded to relief needs in light of the devastating earthquake at the time. Since then MCC has invested in a number of communities throughout Guatemala in various capacities, one of which has been the development of service and learning opportunities aimed at exposing and connecting students/participants in the global north with the people and issues within the global south. As researchers of service learning, who are also committed to a faith tradition and have participated in or have been in relationship with MCC in some capacity, we are interested in evaluating how their faith tradition has helped to both construct their practice as well as critique it. One of the aims of our research is to collaborate with MCC practitioners in assessing and examining their current practice of service/learning in Guatemala in an effort to discover ways in which they are creating opportunities for positive societal change – both in the lives of the student/ participants and the communities in Guatemala, while critiquing the traditional colonial and neocolonial approaches to development.